Efisiensi Pengolahan Persediaan Bearing dengan Metode Economic Order Quantity pada Departemen Gudang di Pt. Xyz - Simbolon, Oky; Sanusi, Aceng Ahmad (Jurnal sosial dan sains, 2025)
This research aims to improve the efficiency of bearing spare parts inventory management at PT. XYZ by applying the Economic Order Quantity (EOQ) method. Optimal spare parts availability is crucial to maintaining smooth production processes, reducing machine downtime, and minimizing inventory costs. PT. XYZ frequently faces issues due to inadequate stock, which hinders machine repairs and increases production costs. This study applies the EOQ method to determine the optimal order quantity for spare parts and the ideal ordering frequency to minimize total inventory costs. The results show that using the EOQ method, the optimal order quantity for bearings is 105.15 units, with an order frequency of 5 times per year. Additionally, the recommended safety stock is 5 units, with a reorder point set at 55 units. The implementation of the EOQ method successfully reduced total inventory costs from Rp 509,400 to Rp 378,600, representing a savings of 25.7%. These findings indicate that the EOQ method offers an effective solution to optimizing inventory management at PT. XYZ, improving production efficiency, and significantly lowering operational costs.